2016
DOI: 10.4236/ojgen.2016.61004
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Linkage Map and Comparative Genome Analysis for the Atlantic Killifish (<i>Fundulus heteroclitus</i>)

Abstract: Genetic linkage maps are valuable tools in evolutionary biology; however, their availability for wild populations is extremely limited. Fundulus heteroclitus (Atlantic killifish) is a non-migratory estuarine fish that exhibits high allelic and phenotypic diversity partitioned among subpopulations that reside in disparate environmental conditions. An ideal candidate model organism for studying gene-environment interactions, the molecular toolbox for F. heteroclitus is limited. We identified hundreds of novel mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…Genotyping was conducted using microsatellite and single nucleotide polymorphism (SNP) markers, identified as polymorphic in the parental (P) generation in each cross, selected from the dense panel of genetic markers used to create the first genetic map for this species (Waits et al . ). Statistical analysis identified highly significant phenotype‐to‐genotype associations, characterized as logarithm of odds of linkage (LOD) scores, which measure the strength of evidence for the presence of a QTL (Van Ooijen ).…”
Section: Methodsmentioning
confidence: 97%
See 3 more Smart Citations
“…Genotyping was conducted using microsatellite and single nucleotide polymorphism (SNP) markers, identified as polymorphic in the parental (P) generation in each cross, selected from the dense panel of genetic markers used to create the first genetic map for this species (Waits et al . ). Statistical analysis identified highly significant phenotype‐to‐genotype associations, characterized as logarithm of odds of linkage (LOD) scores, which measure the strength of evidence for the presence of a QTL (Van Ooijen ).…”
Section: Methodsmentioning
confidence: 97%
“…QTL were annotated using recently developed killifish genomic resources, including gene models for F. heteroclitus (https://my.mdibl.org/display/FGP/Home; NSF DEB‐1120512) and the first killifish genetic map (Waits et al . ). In addition, orthology and conserved syntenic relationships between fish species provided further support for the identification of putative tolerance genes.…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…Segregation distortion is a phenomenon that genotype frequencies at a locus deviate from their Mendelian expectations [35], and it is considered to be a feature of genetic maps in many species, such as red drum [6], Atlantic Killifish [36], bighead carp [37], and Nile tilapia [38]. Many studies have already reported that inclusion of distorted markers in map construction has slight impact on the accuracy for determining maker orders and map length [39,40].For better understanding the distribution pattern of segregation distortion between the two sexes in S. chuatsi, all the distorted markers were retained and used to reconstruct the sex-specific maps.…”
Section: Discussionmentioning
confidence: 99%